Safer Healthcare Strategies for the Real World - Vincent, Charles; Amalberti, René (Springer International Publishing : Imprint: Springer, 2016)
The authors of this book set out a system of safety strategies and interventions for managing patient safety on a day-to-day basis and improving safety over the long term. These strategies are applicable at all levels of the healthcare system from the frontline to the regulation and governance of the system. There have been many advances in patient safety, but we now need a new and broader vision that encompasses care throughout the patient's journey. The authors argue that we need to see safety through the patient's eyes, to consider how safety is managed in different contexts and to develop a wider strategic and practical vision in which patient safety is recast as the management of risk over time. Most safety improvement strategies aim to improve reliability and move closer toward optimal care. However, healthcare will always be under pressure and we also require ways of managing safety when conditions are difficult. We need to make more use of strategies concerned withdetecting, controlling, managing and responding to risk. Strategies for managing safety in highly standardised and controlled environments are necessarily different from those in which clinicians constantly have to adapt and respond to changing circumstances. This work is supported by the Health Foundation. The Health Foundation is an independent charity committed to bringing about better health and health care for people in the UK. The charity's aim is a healthier population in the UK, supported by high quality health care that can be equitably accessed. The Foundation carries out policy analysis and makes grants to front-line teams to try ideas in practice and supports research into what works to make people's lives healthier and improve the health care system, with a particular emphasis on how to make successful change happen. A key part of the work is to make links between the knowledge of those working to deliver health and health care with research evidenceand analysis. The aspiration is to create a virtuous circle, using what works on the ground to inform effective policymaking and vice versa. Good health and health care are vital for a flourishing society. Through sharing what is known, collaboration and building people's skills and knowledge, the Foundation aims to make a difference and contribute to a healthier population.